How issues get framed and reframed when different communities meet: a multilevel analysis of a collaborative soil conservation initiative in the Ecuadorian Andes - Dewulf, Art; Craps, M.; Dercon, G. (Wiley, 2004)
Drawing on qualitative data from a longitudinal case study of a collaborative soil conservation initiative in southern Ecuador, we study how multiple actors, including university experts, development organizations and local communities, make sense of the issues from different perspectives through the process of issue framing. Starting from an analysis of the actors' usual issue frames, we point out their differences in selecting aspects, connecting them and drawing boundaries around the issues. Bringing in the time dimension leads us to consider how changing patterns of actor involvement and evolving frame configurations mutually influence each other. In a third step, we zoom in on the here‐and‐now level of ongoing interaction using discourse analysis, outlining an interactive, communicative and discursive approach to dealing with differences in issue framing. We identify various ways of dealing with these differences and argue that approaching them constructively by tuning the different frames into a mutually acceptable configuration is an important challenge for any attempt at integrated management of natural resources.